A Synopsis of African Metellina (Aranei, Tetragnathidae, Metainae) with Description of a New Species from South Africa - Marusik Y.; Larsen N. (National Academy of Sciences of Ukraine, 2022)
Until this study, Metellina Chamberlin et Ivie, 1941 was unknown in Africa and adjacent islands. A survey of the literature revealed that among nine species of Meta C. L. Koch, 1836 described from the region, two were misplaced in Metainae and actually belong to Tetragnatha Latreille, 1804: T. maculata Blackwall, 1865 (originally placed in the genus Tetragnatha) and Tetragnatha vacillans (Butler, 1876), comb. n. Meta meruensis Tullgren, 1910 misplaced in this genus, most likely belongs to Leucauge White, 1841 or a related genus. Six species are transferred from Meta, and new combinations are established for them: Metellina barreti (Kulczyński, 1899), comb. n., M. gertschi (Lessert, 1938), comb. n., M. longipalpis (Pavesi, 1883), comb. n., M. merianopsis (Tullgren, 1910), comb. n., M. minima (Denis, 1953), comb. n. and M. villiersi (Denis, 1955), comb. n. Metellina haddadi sp. n. is described from the foothills of the Table Mountain near Cape Town. The distribution of all species treated in this paper is mapped.